1957
DOI: 10.1113/jphysiol.1957.sp005714
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inhibition of amine oxidase in vivo on administered adrenaline, noradrenaline, tyramine and serotonin

Abstract: Zeller & Barsky (1952) showed that 0.1 mM/kg of 1-isonicotinyl-2-isopropyl hydrazine (IIH or Marsilid) injected subcutaneously into rats completely inhibited amine oxidase activity in homogenates of liver taken from animals killed after two hours. Larger amounts (0I18 mM/kg) reduced activity in guineapig liver to 6 % of normal. Zeller, Barsky & Berman (1955) state that 0 4 mM/kg completely inhibited liver homogenate activity in the dog but that brain amine oxidase was only reduced by 73 % in the same period o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1957
1957
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…These substances were chosen because of their apparent potency and because others like ephedrine which have an affinity for the same receptors as the transmitter could not be used as they might act in the same way as dibenzyline. The ability of iproniazid to penetrate cells has been questioned by Udenfriend, Weissbach & Bogdanski (1957), who attribute to this property their failure to demonstrate any activity of this substance in vivo, although Koelle & Valk (1954) and Corne & Graham (1957) did obtain evidence of its power to penetrate cells. It seems unlikely that both choline-p-tolyl ether and propamidine should be ineffective for the same reason, and this applies with particular force to propamidine which NORADRENALINE FROM INTESTINES is a powerful liberator of histamine and probably acts, therefore, within the cell.…”
Section: Discussionmentioning
confidence: 99%
“…These substances were chosen because of their apparent potency and because others like ephedrine which have an affinity for the same receptors as the transmitter could not be used as they might act in the same way as dibenzyline. The ability of iproniazid to penetrate cells has been questioned by Udenfriend, Weissbach & Bogdanski (1957), who attribute to this property their failure to demonstrate any activity of this substance in vivo, although Koelle & Valk (1954) and Corne & Graham (1957) did obtain evidence of its power to penetrate cells. It seems unlikely that both choline-p-tolyl ether and propamidine should be ineffective for the same reason, and this applies with particular force to propamidine which NORADRENALINE FROM INTESTINES is a powerful liberator of histamine and probably acts, therefore, within the cell.…”
Section: Discussionmentioning
confidence: 99%
“…The present results showed that the junction potentials were depressed by inhibition of MAO. However, the depressive effect of MAO inhibition on adrenergic transmission at the level of the postsynaptic membrane is not unusual, since a few inves tigators have demonstrated that inhibition of MAO failed to potentiate the action of noradrenaline administered exogenously or released by nerve stimulation (11,15). In hibition of the enzyme also does not increase the out-flow of noradrenaline from cat spleen during sympathetic nerve stimulation (12).…”
Section: Discussionmentioning
confidence: 99%
“…This possibility was investigated by studying the effect of an inhibitor of monoamine oxidase on the output of sympathin at 10 and 30/sec. isoNicotinylisopropyl hydrazine (iproniazid, Marsilid, Roche Products) was given intravenously in amounts known to inhibit monoamine oxidase (Corne & Graham, 1957). No difference was found in the output of noradrenaline before and after Marsilid at either frequency.…”
Section: Effect Of the Frequency Of Stimulation On Outputmentioning
confidence: 99%